Risco de crédito – o impacto da variação do preço de petróleo nas instituições financeiras bancárias. Caso de estudo: Angola - Garcia, Analdete Mami Nuamietu Andrade (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management